A two scale cellular automaton for flow dynamics modeling (2CAFDYM) - Kassogué, Hamidou; Bernoussi, Abdessamed; Maâtouk, Mustapha; Amharref, Mina (Applied Mathematical Modelling, 2017)
• A cellular automaton model for flow dynamics is proposed in a 2.5D form.• A decision aided software is proposed for flow process in 2D or 3D scene.• An application to a basin of northern morocco is considered.• Flood events are discussed with potentially vulnerable areas to flood. In this paper we propose a Two scale Cellular Automaton for Flow DYnamics Modeling (2CAFDYM) in a lowland region. Cells are terrain meshes with a predefined size, arranged in a bi-dimensional hexagonal lattice. The state of the cell consists of two scales: groundwater and surface water, in order to combine flows over saturated soil (Dunne flow) and flows exceeding the infiltration capacity (Hortonian flow). This allows for survey flood events and water resources. Each cell has intrinsic terrain attributes: altitude, soil type and land use. The obtained slopes are considered towards all the neighboring cells such that water flows simultaneously in multiple directions during the same time step. This helps us characterize laminar and turbulent flows. The model is subjected to climatic constraints: rainfall and temperature. The flow dynamics are regulated by mass conservation laws on hydraulic balance sheets (received, evaporated, infiltrated and drained water). Using Java Object Oriented Programming we have designed decision-aided software for the real-time monitoring of flow processes in 2D or 3D scenes through 2CAFDYM. We give some simulations for a basin in northern Morocco covering 34.3 km2, including some areas that are potentially vulnerable to flooding. Digital terrain models, geological maps and satellite images are used to extract input data.